Friendship Bench intervention to address depression and improve HIV care engagement among adolescents living with HIV in Malawi: Study protocol for a pilot randomized controlled trial - Thuy Thi Dieu Dao; Bradley N. Gaynes; Brian W. Pence; Steven M. Mphonda; Kazione Kulisewa; Michael Udedi; Melissa A. Stockton; Jack Kramer; Katherine Grace Waddell; Maria Faidas; Hillary Mortensen; Nivedita L. Bhushan (PLoS ONE, 2025)
Background Adolescents in Sub-Saharan Africa are disproportionately affected by the HIV epidemic. Comorbid depression is prevalent among adolescents living with HIV (ALWH) and poses numerous challenges to HIV care engagement and retainment. We present a pilot trial designed to investigate feasibility, fidelity, and acceptability of an a dapted and an e nhanced F riendship B ench intervention (henceforth: AFB and EFB) in reducing depression and improving engagement in HIV care among ALWH in Malawi. Methods Design: Participants will be randomized to one of three conditions: the Friendship Bench intervention adapted for ALWH (AFB, n = 35), the Friendship Bench intervention enhanced with peer support (EFB, n = 35), or standard of care (SOC, n = 35). Recruitment is planned for early 2024 in four clinics in Malawi. Participants: Eligibility criteria (1) aged 13–19; (2) diagnosed with HIV (vertically or horizontally); (3) scored ≥  13 on the self-reported Beck’s Depression Inventory (BDI-II); (4) living in the clinic’s catchment area with intention to remain for at least 1 year; and (5) willing to provide informed consent. Interventions: AFB includes 6 counseling sessions facilitated by young, trained non-professional counselors. EFB consists of AFB plus integration of peer support group sessions to facilitate engagement in HIV care. SOC for mental health in public facilities in Malawi includes options for basic supportive counseling, medication, referral to mental health clinics or psychiatric units at tertiary care hospitals for more severe cases. Outcomes: The primary outcomes are feasibility, acceptability, and fidelity of the AFB and EFB assessed at 6 months and 12 months and compared across 3 arms. The secondary outcome is to assess preliminary effectiveness of the interventions in reducing depressive symptoms and improving HIV viral suppression at 6 months and 12 months. Discussion This pilot study will provide insights into youth-friendly adaptations of the Friendship Bench model for ALWH in Malawi and the value of adding group peer support for HIV care engagement. The information gathered in this study will lead to a R01 application to test our adapted intervention in a large-scale cluster randomized controlled trial to improve depression and engagement in HIV care among ALWH. Trial registration ClinicalTrials.gov ( NCT06173544 )